Correlations of GGT, Hcy and ABI with carotid atherosclerosis in essential hypertension patients: Correlations of GGT, Hcy and ABI with carotid atherosclerosis - Peng, Min; Wu, Yong; Jin, Yingying (Cellular and Molecular Biology, 2023)
This study was to explore the correlations of glutamyltransferase (GGT), homocysteine (Hcy) and ankle-brachial index (ABI) with the onset of cervical atherosclerosis (CAS) in essential hypertension (EH) patients. For this purpose, a total of 280 EH patients who were admitted to this hospital or visited the clinic of this hospital were enrolled into the EH group and received the color Doppler ultrasound for carotid artery and biochemical test for blood, and according to the plaques, they were divided into three groups: non-plaque group (n = 113), stable plaque group (n = 102) and non-stable plaque group (n = 65). Simultaneously, 80 healthy subjects who underwent the physical examination were enrolled in the control group. Correlations of GGT, Hcy and ABI with the onset of CAS were analyzed. The results indicated that in the EH group, the prevalence of CAS and Hcy levels were all higher than those in the control group (all P<0.05). As compared to the non-plaque group, patients with stable or non-stable plaques had higher levels of GGT and Hcy in serum but lower levels of ABI (all P<0.05). Logistic regression analysis revealed that CAS plaques were in positive correlation with the levels of GGT and Hcy in serum, but in negative correlation with ABI (P<0.05). In conclusion, ABI is the protective factor of CAS in EH patients, while Hcy and GGT are the negative factors.